Levofloxacin Detection Using l-Cysteine Capped MgS Quantum Dots via the Photoinduced Electron Transfer Process - Hashmi, S. Z. H.; Dhiman, Tarun Kumar; Chaudhary, Navneet; Singh, Avinash Kumar; Kumar, Rahul; Sharma, Jai Gopal; Kumar, Anil; Solanki, Pratima R. (Frontiers in Nanotechnology, 2021)
Antibiotics resistance is becoming one of the biggest problems of the 21st century. The prior detection of antibiotics resistance can help human beings in better treatment of diseases. Here, we have used L-Cysteine capped magnesium sulfide quantum dots (L-Cyst-MgS QDs) for the detection of levofloxacin antibiotic. L-Cyst-MgS QDs were synthesized using the hydrothermal method. Transmission electron microscopy study showed monodispersed L-Cyst-MgS QDs of 2-4 nm in size. Energy dispersive x-ray photoemission spectroscopy study confirmed the elemental composition of the L-Cyst-MgS QDs without any impurity. UV-vis absorption study showed a peak centered around 340 nm. The photoluminescence study shows the maximum peak at 410 nm for 340 nm of excitation wavelength. L-Cyst-MgS QDs were studied with thirteen antibiotics, namely Thiamphenicol, Gentamicin, Erythromycin, Ofloxacin, Ampicillin, Ciprofloxacin, Tetracycline, Chloramphenicol, Florfenicol, Amoxicillin, Moxifloxacin, Norfloxacin, and Levofloxacin. Among these, levofloxacin showed the biggest change in the intensity of the peaks and was further used for the interaction study. In the interaction study, the peak corresponding to MgS showed a continuous decrease, while the peak corresponding to levofloxacin showed the increase with the increased concentrations (0-100 μg/ml) of levofloxacin. Linear behavior was obtained in the range of 1-90 µg/mL. FT-IR study confirmed the interaction of the levofloxacin with L-Cyst-MgS QDs. In the TCSPC study, no change in the lifetime of both the samples was observed, confirming no FRET-based mechanism. The underlying mechanism can be explained based on the electron transfer from the conduction band of the L-Cyst-MgS QDs to the LUMO of levofloxacin.